A Simple Elastoplastic Damage Constitutive Model of Porous Rock Materials - Chao, Chen; Yajun, Cao; Yanli, Jin; Xuelei, Duan; Shifan, Liu; Kuan, Zhang (Frontiers in Physics, 2022)
Traditional macroscopic phenomenon constitutive model is not easy to describe in the non-linear mechanical properties of porous rock materials, since the effect of porosity does not incorporate into the strength criterion. This paper presents a simple elastoplastic damage constitutive model of porous rock material based on micromechanical theory. To consider the heterogeneities of the studied porous rock, a simplified representative volume element is introduced, and it is assumed that it is made up of randomly distributed spherical pores embedded in a solid matrix obeying Drucker-Prager yield function. Thus, a homogenized plastic criterion considering the effect of porosity is introduced to describe the macroscopic plastic mechanical properties of porous rock materials. In this model, the non-associated flow rule and isotropic strain hardening law are used, and then the degradation of elastic and plastic properties is employed by adopting a damage criterion. This criterion is related to the evolution of equivalent plastic strain. In order to verify the accuracy of the model, the corresponding numerical program was used to realize the micro-macro constitutive model, and the results were compared with the triaxial compression test results of sandstone under different confining pressures. It is observed that the numerical simulation results are in great agreement with the experimental data, indicating that the proposed model is able to predict the main mechanical behavior of porous sandstone.